SUSTAINABILITY WINDOW APPROACH FOR FISHERIES MANAGEMENT AT THE COASTAL AREA OF TERNATE ISLAND, NORTH MALUKU PROVINCE - Faizal Rumagia; Mennofatria Boer; Rahmat Kurnia; Mohammad Mukhlis Kamal (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2020)
Aims: This study aims to assess the value sustainable development opportunity of the coral reef fisheries activities in Indonesia from the ecological, economic, and social aspect, with a case study of coral reef fisheries at the coastal area of Ternate Island, using the Sustainability Window (SuWi) approach. Methodology and Results: The data was collected from statistical data from relevant institutions and literature study, which consists of ecological, economic and social data, and analyzed using the Sustainability Window approach to determine the sustainability of the fisheries development. The result shows that the Sustainability Window of the coral reef fisheries in the research area tends to move towards sustainable development, where the national policy in catch fisheries management has an impact on the sustainable development and management of coral reef fisheries at the coastal area of Ternate Island. Conclusion, significance and impact study: The Sustainability Window of coral reef fisheries at the coastal area of Ternate Island tends to move towards sustainable processes, with the width of sustainability window that not too narrow to the coral reef fisheries activities at the provincial and national levels. This condition attaches strings to a precautionary approach in policy decision for the management process, and consideration to the effect that can result from the development policy, both at the provincial and national level. The use of Sustainability Windows approach can provide a new simple way for assessing whether the development has been towards a more sustainable direction or not.